pH-Mediated Single Molecule Conductance of Cucurbit[7]uril - Ai, Qiushuang; Fu, Qiang; Liang, Feng (Frontiers in Chemistry, 2020)
Recognition tunneling technique owns the capability for investigating and characterizing molecules at single molecule level. Here, we investigated the conductance value of cucurbit[7]uril (CB[7]) and melphalan@CB[7] (Mel@CB[7]) complex molecular junctions by using recognition tunneling technique. The conductances of CB[7] and Mel@CB[7] with different pH values were studied in aqueous media as well as organic solvent. Both pH value and guest molecule have an impact on the conductance of CB[7] molecular junction. The conductances of CB[7] and Mel@CB[7] both showed slightly difference on the conductance under different measurement systems. This work extends the molecular conductance measurement to aqueous media and provides new insights of pH-responsive supramolecular system for single molecule detection through electrical measurements.